2019
DOI: 10.1177/0894845319832129
|View full text |Cite
|
Sign up to set email alerts
|

Work Experiences of Native Americans: A Qualitative Study

Abstract: Few studies have explored the careers of Native Americans. Historically, this population has been, and continues to be, ignored within mainstream career and management studies. To address this research gap, the current study explores the challenges that Native Americans, living and working in various locations and states across the United States, face. Drawing on Syed and Özbilgin’s relational framework, a qualitative approach was used whereby 14 in-depth, semistructured interviews were conducted and analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…However, indigenous students face multi-faceted barriers and challenges in their studies as noted earlier (Hall et al. , 2015; Al-Asfour et al. , 2019; Taylor et al.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…However, indigenous students face multi-faceted barriers and challenges in their studies as noted earlier (Hall et al. , 2015; Al-Asfour et al. , 2019; Taylor et al.…”
Section: Resultsmentioning
confidence: 84%
“…While functionalist theorists admit social inequality as outlined earlier, they might not directly associate the unfair competition in job market imposed on indigenous peoples as the result of functionalist education. Globally, indigenous communities have to deal with lack of job opportunities for their members: Native Americans encounter challenges including inadequate education, lack of job opportunities, lack of transportation, issues in work–life balance and cultural stereotyping and bias (Al-Asfour et al. , 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Malaysian National Graduate Employability Blueprint 2015-2025 highlighted that most fresh graduates were not able to impress in job interviews (Ministry of Higher Education of Malaysia [MHEM], 2019). In line with Malaysian National Graduate Employability Blueprint, Ahmed, Hayfaa and Sandra (2019) noted that lacked of impression skills to demonstrate their capabilities in job interviews.…”
Section: Introductionmentioning
confidence: 92%
“…The investigations mentioned above found that there is an absence of IMTs in job interview appraisals and suggested that investigations into IM should be frequently carried out to establish if prospective interviewees satisfy the present employment requirements. Similar to Ahmed et al (2019), Roulin et al (2015), Roulin (2016), Lars andFanny (2019), Mohd Noor et al (2017) had also investigated the job interview abilities of prospective engineers centered on the utilization of appraisal analysis assessment and verbal impression management. It was established that prospective engineers must possess some vital components like linguistic proficiency (i.e., appropriate application of words and phrases), excellent communication abilities, and IMT to find employment.…”
Section: Past Studies On Impression Management Tacticsmentioning
confidence: 99%